DETERMINANT ANALYSIS OF THE QUALITY OF LOCAL GOVERNMENT FINANCIAL REPORTS WITH THE GOVERNMENT INTERNAL CONTROL SYSTEM AS MODERATING VARIABLES IN THE GOVERNMENT MANDAILING DISTRICT CHRISTMA - Ahmad Zubeir Rangkuti; Eka Nurmala Sari; Widia Astuty (Jurnal Ekonomi, 2022)
The purpose of this study was to determisne and analyze the factors that affecting the quality of financial statements in the Government of Mandailing Natal District. The factors that influence it are the implementation of government accounting standards (SAP), human resource competencies (HR), utilization of the local financial information system (SIKD), and the role of Government Internal Supervisory Apparatus (APIP), with the moderating variables is the government’s internal control system (SPIP). The type of research in this study is causal associative using primary data and data collection techniques through the distribution of questionnaires in regional device organizations of Mandailing Natal, North Sumatera, Indonesia. The method of determining the sample with the census method, so that the entire population is used as a research sample. The population of this study was 35regional device organizations, each consisting of 3 respondents with total 105respondents. Data is processed using SEM method with Smart PLS analysis tools. The results of this study prove that the implementation of SAP has aneffect on the quality of the Mandailing Natal District Government's financial statements, HR competencies have an effect on the quality of the Mandailing Natal District Government's financial statements, the utilization of SIKD has a an effect on the quality of the Mandailing Natal District Government's financial statements, the role of the Government Internal Supervisory Apparatus (APIP)has an effect on the quality of the Mandailing Natal District Government's financial statements. Then SPIP does not moderate each of the effects of SAP implementation, HR competencies, utilization of SIKD and the role of Government Internal Supervisory Apparatus (APIP) on the quality of the Mandailing Natal District Government's financial statements.